Metal Allergy in Tracheostomy Tube Placement Resulting in Complete Subglottic Stenosis: A Case Report. (December 2022) - Bui, Roger; Boven, Lindsay; Kaufman, David; Weinberger, Paul
Objectives: Metal hypersensitivity reaction to surgical implants is a well- known phenomenon that is associated with pain, swelling, inflammation, and decreased efficacy of the implant. We present a unique case of a patient with placement a metal Jackson tracheostomy tube that led to expeditious total subglottic stenosis. Methods: The patient was a 33-year old, severely atopic woman with history of asthma exacerbations requiring several intubations for acute respiratory failure with several subsequent tracheal dilations with steroid injections, and eventual tracheostomy placement with a metal Jackson tracheostomy tube that led to expeditious total subglottic stenosis. Results: Initial intervention included performing an airway evaluation, CO2 laser, and steroid injection of the area of complete subglottic stenosis. Follow up several months later revealed little improvement in level of tracheal narrowing proximal to the tracheostomy tube. Patient did not have shortness of breath but continued to be aphonic. Cricotracheal versus tracheal resection have been proposed but surgical morbidity was deemed too high due to patient's obesity. Conclusions: Metal hypersensitivity reactions are well known phenomena as it relates to surgical implants in other surgical specialties but are seldom reported within the ear, nose and throat literature. Oftentimes, it takes astute observation to diagnose and establish a connection. Prompt recognition and treatment can be acquired from interdisciplinary collaboration with allergy.